Analysis of Law No. 23/2004 and the Ideals of Elimination of Domestic Violence in Indonesia from the Perspective of Sadd adz-Dzari'ah - Muhammad Sunarto; Alfin Haidar Ali; Nadiyah Rofikah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Purpose - This research aims to analyze domestic violence using the concept of sadd adz-dzari'ah to find out whether domestic violence prevention efforts by the PKDRT Law are following the concept of sadd adz-dzari'ah. Methods - The research method in this study is based on the manhaji method, which is a method of solving problems by following the way of thinking and the rules of determining the law that has been compiled by the imam madzhab are sadd adz-dzari'ah. Findings - Based on the research results, it can be concluded that domestic violence is an intermediary or dzari'ah that can cause greater harm that must be prevented. Research implications - So the presence of the PKDRT Law is following the concept of sadd adz-dzari'ah because it is a prevention of domestic violence so as not to cause greater harm.